2022
DOI: 10.3389/fmicb.2022.871086
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Ecology and Inferred Functions in Children With ASD Compared to Neurotypical Subjects

Abstract: Autism spectrum disorders (ASDs) is a multifactorial neurodevelopmental disorder. The communication between the gastrointestinal (GI) tract and the central nervous system seems driven by gut microbiota (GM). Herein, we provide GM profiling, considering GI functional symptoms, neurological impairment, and dietary habits. Forty-one and 35 fecal samples collected from ASD and neurotypical children (CTRLs), respectively, (age range, 3–15 years) were analyzed by 16S targeted-metagenomics (the V3–V4 region) and infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 130 publications
3
24
1
Order By: Relevance
“…37 The abundance of Roseburia was increased in ASD children compared with the control group, and Roseburia was associated with gastrointestinal symptoms associated with ASD. 38 The synbiotic intervention significantly reduced the abundance of harmful bacteria in ASD mice, such as Odoribacter and Roseburia (Fig. 4).…”
Section: Discussionmentioning
confidence: 95%
“…37 The abundance of Roseburia was increased in ASD children compared with the control group, and Roseburia was associated with gastrointestinal symptoms associated with ASD. 38 The synbiotic intervention significantly reduced the abundance of harmful bacteria in ASD mice, such as Odoribacter and Roseburia (Fig. 4).…”
Section: Discussionmentioning
confidence: 95%
“…Sutterella , identified as a microbial biomarker for ASD patients in linear discriminant effect size analysis, is a principal bacterial genus implicated in the increased risk of ASD, a finding consistent with our results [ 59 ]. The study by Williams et al also indicated a higher abundance of Sutterella in children with ASD [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sutterella , an acetate producer, could be involved in neurodevelopmental disorders such as autism spectrum disorder (ASD) [ 49 , 50 ], gastrointestinal (GI) diseases, including inflammatory bowel disease (IBD) and coeliac disease (CD), and their comorbidities, such as cardiovascular disease and obesity [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%